Generating family farming revenue through juvenile fish production: a case study in native species - Adriana Fernandes de Barros; Angélica Neves Vieira; Rafael Alexandre Costa e Silva; Caio Francisco Santana Farias; Soraia Andressa Dall’Agnol Marques; Maurício Laterça Martins (Acta Scientiarum: Animal Sciences)
In view of the need to improve the development of family production enterprises, zootechnical and economic planning were conducted in a rural settlement in 0.78 ha of water depth for the rearing and marketing of juveniles of the tambatinga hybrid (♀ tambaqui Colossoma macropomum x ♂ pirapitinga Piaractus brachypomus) to verify its economic viability. For the zootechnical indicators, a 16-month production cycle was determined, with three juvenile production cycles and two fattening cycles. For the remaining fish that were not sold, the quantity of initial and final fish, stock biomass, average initial and final weight, apparent feed conversion, and mortality rate were determined. For economic planning, a total operating cost methodology was adopted to determine the costs per unit of production, gross revenue, gross margin, net profit, and profitability index. The production of juveniles of many sizes is economically viable for family farming, showing attractive profitability indicators even under adverse zootechnical conditions. This study demonstrated the effectiveness of zootechnical and economic planning on a property that can optimize production and use of the area, as well as showing producers how rewarding it is to farm fish.